Decomposition of calcium carbonate in cockle shell - Ahmad Hamidi, Ahmad Hamidi (2013)
Cockle shell or scientifically known as Anadara granosa is a local bivalve mollusc having a rounded shell with radiating ribs. The production of cockle shell in Malaysia was great and keeps increasing by year. In Malaysia, cockle shell was treated as waste with unpleasant smell and mostly left to natural deteriorates. Small number of study utilizes cockle shell as source of CaO. Hence, this study was conducted to propose a cockle shell as an alternative source of CaCO3 by the calcination process. Calcination of CaCO3 is a process of producing CaO which is subjecting a substance to the action of heat. This will done by using a muffle furnace. However, the efficiency of the process depends on the variable involved. Therefore, this paper aims to illustrate the effects of few variables on calcination reaction of CaCO3 via thermal gravimetric analyzer (TGA) in order to optimize the process. In the present work, the vast availability of waste resources in Malaysia which is cockle shell were used as CaCO3 sources. The experimental variables such as particle size, temperature and heating rate is put under study toward decomposition rate. The decomposition of calcium carbonate was investigated by using a particle size with 300, 425-600, and 1180m in thermal gravimetric analyzer (TGA). The experiments were test with different temperature (700, 800 and 900C) to study the decomposition rate of CaCO3. Experiment has been conducted in inert atmosphere (N2 gas). Analysis of XRF was conducted to determine the mineral composition of powder cockle shell. The surface morphology of raw cockle shell and calcined cockle shell was illustrated by SEM. Mineral composition of cockle shell by XRF showed that cockle shell was made up of 59.87% calcium (Ca). Thermal gravimetric data shows that smaller particle size experienced rapid weight loss compared to larger particle. The higher calcination temperature promotes higher calcination rate as this will increase the particles kinetic energy and thus, accelerates decomposition of CaCO3 to CaO. The SEM analysis conclude that the higher calcination temperature give the structure of the sample more porous. Hence, more CO2 will be released to give the more conversion to CaO